Assessment of preoperative anxiety and depression in patients with pulmonary ground-glass opacities: Risk factors and postoperative outcomes - Han, Yu; Yu, Qiduo; Ma, Qianli; Zhang, Jin; Shi, Yuhui; Zhang, Zhenrong; Qiang, Guangliang; Xiao, Fei; Liang, Chaoyang (Frontiers in Surgery, 2023)
Objective: A large number of patients with pulmonary ground-glass opacities (GGOs) have anxiety and depression. However, the contributing factors and effects of anxiety and depression on postoperative outcomes are still unclear. Methods: Clinical data for patients undergoing surgical resection for pulmonary GGOs were collected. We prospectively evaluated levels and risk factors for anxiety and depression in patients with GGOs before surgery. The relationship between psychological disorders and postoperative morbidity was evaluated. Quality of life (QoL) was also assessed. Results: A total of 133 patients were enrolled. Prevalence rates of preoperative anxiety and depression were 26.3% (n=35) and 18% (n=24), respectively. Multivariate analysis revealed depression (odds ratio[OR]=16.27, P<0.001) and multiple GGOs (OR=3.146, P=0.033) to be risk factors for preoperative anxiety. Anxiety (OR=52.166, P<0.001), age>60 (OR=3.601, P=0.036), and unemployment (OR=8.248, P=0.006) were identified as risk factors for preoperative depression. Preoperative anxiety and depression were associated with lower QoL and higher postoperative pain scores. Our results also revealed that the incidence of postoperative atrial fibrillation was higher in patients with than in those without anxiety. Conclusions: In patients with pulmonary GGOs, comprehensive psychological assessment and appropriate management are required before surgery to improve QoL and reduce postoperative morbidity.